Peran Birokrasi dalam Program Keluarga Harapan (PKH) di Kabupaten Pati Tahun 2025 (Studi Kasus : Dinsos P3AKB Kabupaten Pati) - Mardiana Tri Anjarwati; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2026)
Program Keluarga Harapan (PKH is one of the Indonesian government's policies aimed at poverty alleviation through conditional social assistance for poor and vulnerable families. However, several challenges remain in its implementation, including inaccuracies in beneficiary data, weak data updating processes, and suboptimal coordination and administrative systems. These issues indicate that the effectiveness of the program is determined not only by the policy itself but also by the role of bureaucracy in its implementation. This study aims to analyze the role of bureaucracy in the implementation of the Family Hope Program (PKH) in Pati Regency. The study employs Max Weber's bureaucratic theory, which consists of hierarchy, formal rules and legality, impersonality, and administration. A qualitative method with a descriptive approach was used. Data were collected through interviews, observation, and documentation and were systematically analyzed based on the indicators of the selected theoretical framework. The findings show that the implementation of PKH in Pati Regency reflects the application of bureaucratic principles, although it has not yet been fully optimal. In terms of hierarchy, the organizational structure and division of responsibilities have functioned well, despite challenges in coordination and reporting. Regarding formal rules and legality, the implementation of the program has been carried out in accordance with applicable regulations and technical guidelines. In terms of impersonality, the implementation of PKH demonstrates the application of objectivity through the use of beneficiary eligibility criteria and the performance of facilitators' duties in accordance with program regulations. In the administrative aspect, data management and reporting systems have been implemented, but data updating and integration remain less than optimal. Therefore, strengthening the administrative system, especially through regular data updating and integration, is necessary. In addition, improving coordination among implementers, strengthening control mechanisms, and optimizing community oversight through routine meetings are essential to support a more effective and well-targeted implementation of the program.